Stable isotope study of a new chondrichthyan fauna (Kimmeridgian, Porrentruy, Swiss Jura): an unusual freshwater-influenced isotopic composition for the hybodont shark Asteracanthus - Leuzinger, Léa Sylvia (2015)
Chondrichthyan teeth (sharks, rays and chimaeras) are mineralised in isotopic equilibriumwith the surrounding water, and parameters such as water temperature andsalinity can be inferred from the oxygen isotopic composition (18Op) of their bioapatite.We analysed 5 a new chondrichthyan assemblage, as well as teeth from bony fish(Pycnodontiformes). All specimens are from Kimmeridgian coastal marine deposits ofthe Swiss Jura (vicinity of Porrentruy, Ajoie district, NW Switzerland). While the overallfaunal composition and the isotopic composition of bony fish are consistent with marineconditions, unusually low 18Op values were measured for the hybodont shark Astera10canthus. These values are also lower compared to previously published data from olderEuropean Jurassic localities. Additional analyses on material from Solothurn (Kimmeridgian,NW Switzerland) also have comparable, low-18O isotopic compositions forAsteracanthus. The data are hence interpreted to represent a so far unique, freshwaterinfluencedisotopic composition for this shark that is classically considered as a marine15 genus. While reproduction in freshwater or brackish realms is established for other hybodonts,a similar behaviour for Asteracanthus is proposed here. Regular excursionsinto lower salinity waters can be linked to the age of the deposits and correspond toan ecological adaptation, most likely driven by the Kimmeridgian transgression andby the competition of the primitive shark Asteracanthus with the rapidly diversifying20 neoselachians (modern sharks).